PENDEKATAN FENOMENOLOGI DALAM PENDIDIKAN ISLAM PERSPEKTIF RICHARD C. MARTIN - MUHAMMAD ALFIAN; INDAH HERNINGRUM; MUHAMMAD FAJRUL BAHRI (stit-islamic-village, 2020)
This article aimed to study one of the phenomenological approaches proposed by Richard C. Martin. Religion is a complicated thing to be studied. Since Islam as a multi-dimensional religion requires a comprehensive study through methods and approaches. Generally, Richard C. Martin stated that religion is a social phenomenon that arises or is intentionally raised to regulate the goodness of human life. Commonly, this kind of approach is still unacceptable, but it should be considered as a research object for academics (khawas). Especially in Islamic education academics. The authors employed library research method to further elaborate on Richard C. Martin's thought in his phenomenological approach. The approach used is a descriptive qualitative approach.